2013
DOI: 10.1021/am4042355
|View full text |Cite
|
Sign up to set email alerts
|

On–Off–On Fluorescent Carbon Dot Nanosensor for Recognition of Chromium(VI) and Ascorbic Acid Based on the Inner Filter Effect

Abstract: Chromium(VI) [Cr(VI)] is considered as a severe environmental pollutant, due to its highly toxic and carcinogenic properties. Therefore, low cost, highly sensitive sensors for the determination of Cr(VI) are highly demanded. It is well-known that highly luminescent carbon dots (CDs) have been successfully applied as fluorescent nanosensors for pH, ions, and molecular substances. In the present work, we have demonstrated an on-off fluorescent CD probe for detecting Cr(VI) based on the inner filter effect (IFE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
317
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 734 publications
(331 citation statements)
references
References 42 publications
12
317
0
Order By: Relevance
“…In this report, CA is still chosen as carbon source and DETA as N source for synthesis of N-GQDs. When the reaction is carried out in the water solution, the as-obtained N-GQDs show the blue emission (named as N-GQDs-B) as previous reports 27,28 . Instead of the water with DMF, the N-GQDs exhibit strong green light emission under excitation wavelength of 460 nm (denoted as N-GQDs-G).…”
Section: Resultssupporting
confidence: 72%
“…In this report, CA is still chosen as carbon source and DETA as N source for synthesis of N-GQDs. When the reaction is carried out in the water solution, the as-obtained N-GQDs show the blue emission (named as N-GQDs-B) as previous reports 27,28 . Instead of the water with DMF, the N-GQDs exhibit strong green light emission under excitation wavelength of 460 nm (denoted as N-GQDs-G).…”
Section: Resultssupporting
confidence: 72%
“…When the X-rays interacts with a crystallite C-dots sample, the constructive interference is produced, and these diffracted X-rays are then detected, processed, and counted, revealing the average structure of C-dots [86,87,89,[130][131][132][133][134][135][136]. Figure 3(A) displays a typical XRD pattern of polyethylenimine (PEI) functionalized C-dots (C-dots-PEI) derived from microwave-assisted pyrolysis of glycerol in the presence of branched PEI [86].…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…It has been reported that the decreased fluorescence intensity of fluorophore was attributed to the absorption spectrum of the absorber, which has an overlap with the excitation and/or emission spectrum of the fluorophore, i.e., inner filter effect. 32,34 The amino groups of the HPAMAM were able to interact with Cu 2+ to form cupric amine complexes that acted as an absorber, leading to a selective quenching of the fluorescence intensity of HPAMAM by the inner filter effect.…”
Section: Fluorescence Response Of the Hpamam Toward The Cu 2+ And Mecmentioning
confidence: 99%
“…As shown in Scheme 1, Cu 2+ ions could bind to the amino groups of the HPAMAM to form cupric amine complexes, resulting in the fluorescence intensity of HPAMAM quenching by the inner filter effect, 31 caused by the absorption of the excitation and/or emission light by absorbers in the detection system. [32][33][34] Based on this, we designed a label-free, rapid, selective and sensitive fluorometric method to detect Cu 2+ ions in aqueous media by using HPAMAM. Furthermore, the practicality of this novel method based on the HPAMAM probe to detect Cu 2+ ions in real water samples also proved successful.…”
Section: Introductionmentioning
confidence: 99%